Peak Last Glacial weathering intensity on the North American continent recorded by the authigenic Hf isotope composition of North Atlantic deep-sea sediments - Gutjahr, Marcus; Frank, Martin; Lippold, Jörg; Halliday, Alex N. (Quaternary science reviews, 2014)
We have retrieved radiogenic hafnium (Hf) isotope compositions (ɛHf) from authigenic Fe-Mn oxyhydroxides of deep northwest Atlantic sediments deposited over the past 26 ka to investigate the oceanic evidence of changes in dissolved weathering inputs from NE America during the last deglaciation. The extraction of seawater-derived Hf isotopic compositions from Fe-Mn oxyhydroxides is not a standard procedure. Comparisons between the Al/Hf ratios and Hf isotopic compositions of the chemically extracted authigenic phase on the one hand, and those of the corresponding detrital fractions on the other, provide evidence that the composition of past seawater has been reliably obtained for most sampled depths with our leaching procedures. This is endorsed most strongly by data for a sediment core from 4250 m water depth at the deeper Blake Ridge, for which consistent replicates were produced throughout. The Hf isotopic composition of the most recent sample in this core also closely matches that of nearby present day central North Atlantic seawater. Comparison with previously published seawater Nd and Pb isotope compositions obtained on the same cores shows that both Hf and Pb were released incongruently during incipient chemical weathering, but responded differently to the deglacial retreat of the Laurentide Ice Sheet. Hafnium was released more congruently during peak glacial conditions of the Last Glacial Maximum (LGM) and changed to typical incongruent interglacial ɛHf signatures either during or shortly after the LGM. This indicates that some zircon-derived Hf was released to seawater during the LGM. Conversely, there is no clear evidence for an increase in the influence of weathering of Lu-rich mineral phases during deglaciation, possibly since relatively unradiogenic Hf contributions from feldspar weathering were superimposed. While the authigenic Pb isotope signal in the same marine sediment samples traced peak chemical weathering rates on continental North America during the transition to the Holocene a similar incongruent excursion is notably absent in the Hf isotope record. The early change towards more radiogenic ɛHf in relation to the LGM may provide direct evidence for the transition from a cold-based to a warm-based Laurentide Ice Sheet on the Atlantic sector of North America.
Gesehen am 18.09.2020